"We are all in this together:" police use of social media during the COVID-19 pandemic. Issue 1 (22nd September 2021) - Hu, Xiaochen; Dong, Beidi; Lovrich, Nicholas
Abstract : Purpose: Previous studies consistently indicate that police agencies tend to use social media to assist in criminal investigations, to improve police-community relations and to broadcast both crime- and non-crime-related tips promotive of public safety. To date, little research has examined what content the police tended to post on their social media sites during the COVID-19 pandemic. Design/methodology/approach: By selecting the 14 most widely attended police agencies' Facebook accounts, the current study collects and analyzes a sample of 2, 477 police Facebook postings between February 1 and May 31, 2020. By using a mix-method approach, the study addresses three research questions: 1) What kinds of messages did the police tend to post on their Facebook pages before and during this pandemic? 2) What types of COVID-related police Facebook postings were made? 3) How did the public react to COVID-19-related police Facebook postings? Findings: The findings suggest that the police have come to believe that social media can be used as an effective police−public communicative tool in stressful times. The findings also suggest that social media platforms have become a routinized tool of police−public communications which can, to some appreciable extent, substitute for the in-person contacts traditionally relied upon in community policing. Originality/value: This study of police use of social media explores the question of whether the use of these media can serve as an effective tool to connect the police with the public under circumstances where in-person contacts are greatly constrained. Some public policy implications emerging from the findings reported are discussed, along with implications for further research along these lines.